Atividade da curcumina livre e nanoencapsulada in vitro e in vivo sobre ratos infectados experimentalmente com Trypanosoma evansi - Gressler, Lucas Trevisan (2014)
The aim of this study was to evaluate the in vitro and in vivo trypanocidal activity of free curcumin (F-C) and curcumin-loaded lipid-core nanocapsules (C-LNCs) against Trypanosoma evansi, as well as its antioxidant activity in vivo. In vitro tests were performed in culture medium containing T. evansi, using eight concentrations of F-C (100, 75, 50, 25, 12.5, 6.25, 3.12, 1.56 and 0.78 mg mL-1), and four concentrations of C-LNCs (100, 75, 50, 25 mg mL-1). The counting of alive parasites was performed in a Neubauer chamber after 1, 3, 6, 9 and 12 hours of incubation. In vitro tested showed the death of all trypanosomes treated with F-C one hour post-incubation (PI), except at concentrations below 6.25 mg mL-1. Mobile trypanosomes, treated with C-LNCs, were observed until the third hour PI, except at the highest concentration. For in vivo tests, 54 animals were divided into 8 groups (A, B, C, D, E, F, G and H), as follows: group A (not infected and treated with saline); B (not infected and treated with C-LNCs); C (infected with T. evansi and treated with blank nanocapsules of curcumin); D (infected with T. evansi and treated with DMSO ); E (infected with T. evansi and treated with saline); F ( infected with T. evansi and treated with C-LNCs at a dose of 10 mg.kg); G (infected with T. evansi and treated with F-C at a dose of 10mg/kg) and H (infected with T. evansi and treated with F-C at a dose of 100mg/kg). The results showed that the animals treated with curcumin presented a lower parasitemia compared with untreated animals. Additionally, infected animals showed an increase of nitrite/nitrate and protein peroxidation, while the infected animals, that received treatment based on curcumin, showed a reduction in these parameters. Infected groups treated with curcumin exhibited a reduction in ALT and creatinine levels when compared with the positive control group. Therefore, it was possible to conclude that F-C and C-LNCs showed trypanocidal activity in vitro; however, the curcumin in its free form appeared to be more effective. A control of parasitemia was observed in in vivo tests for the treated groups, besides a possible protective effect of curcumin on liver and kidney functions, which also would be related to the antioxidant phytochemical action proved in our study.